Pengaruh Inovasi Pengadaan Barang/Jasa terhadap Kinerja Pejabat Pembuat Komitmen melalui Mediasi Pemberdayaan Pegawai dan Kepuasan Pengguna di Pemerintah Daerah Kabupaten Lebak - Djumiyanto, Teddy; Lutfi, Lutfi (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
There is a change in Perpres 54/2010 to Perpres 16/2018 which adds to the burden of the Commitment Making Officers (PPK), to support the addition of the PPK workload and the principles of procurement are fulfilled, the Lebak Regency Government innovates the procurement namely the process of increasing the performance of PPK in an effort to fulfill the principles of procurement with the support of internal services and electronic services through the e-Procurement information system. This study aims to determine the effect of in procurement innovation on PPK Performance by mediation of Employee Empowerment and User Satisfaction. This research was conducted in the Lebak Regency Government. The sample used was 86 respondents. Primary data was collected using a questionnaire in the form of a statement and analyzed using Structural Equation Modeling with the help of SmartPLS software. Of the five hypotheses in this study, there are four hypotheses that are accepted and one hypothesis that is rejected. The biggest contribution to PPK Performance is the indirect effect of the Procurement Innovations through User Satisfaction.